2020
DOI: 10.1111/bph.15099
|View full text |Cite
|
Sign up to set email alerts
|

Astaxanthin attenuates hepatic damage and mitochondrial dysfunction in non‐alcoholic fatty liver disease by up‐regulating the FGF21/PGC‐1α pathway

Abstract: Background and Purpose Non‐alcoholic fatty liver disease (NAFLD) is considered to be one of the most common chronic liver diseases across worldwide. Astaxanthin (Ax) is a carotenoid, and beneficial effects of astaxanthin, including anti‐oxidative, anti‐inflammatory, and anti‐tumour activity, have been identified. The present study aimed to elucidate the protective effect of astaxanthin against NAFLD and its underlying mechanism. Experimental Approach Mice were fed either a high fat or chow diet, with or withou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
56
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 95 publications
(57 citation statements)
references
References 64 publications
1
56
0
Order By: Relevance
“…Astaxanthin, a marine carotenoid well-known for its potent antioxidant capacity, effectively prevented hepatic lipid accumulation by down-regulating lipogenic genes and improved mitochondrial oxidative metabolism by protecting mitochondrial redox homeostasis and functional integrity against oxidative stress [6]. Nitzschia laevis extract (NLE) was found in our previous study to reduce lipid content of C57BL/6J mice [7].…”
Section: Introductionmentioning
confidence: 96%
“…Astaxanthin, a marine carotenoid well-known for its potent antioxidant capacity, effectively prevented hepatic lipid accumulation by down-regulating lipogenic genes and improved mitochondrial oxidative metabolism by protecting mitochondrial redox homeostasis and functional integrity against oxidative stress [6]. Nitzschia laevis extract (NLE) was found in our previous study to reduce lipid content of C57BL/6J mice [7].…”
Section: Introductionmentioning
confidence: 96%
“…Astaxanthin, a xanthophyll carotenoid extracted from seafood, possesses various biological functions including anti‐oxidative and neuroprotective effects (Wu et al, 2015; Wu et al, 2020; Zhang, Wang, et al, 2017). Unlike other carotenoids, astaxanthin contains two additional oxygenated groups on each ring structure with more powerful anti‐oxidant property (Zhang et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Adenosine A2a receptor activation, which is expected to reduce lipotoxicity [387] and suppress inflammatory activation of macrophages [388] , regulated CD4 + T-cells response (proliferation of Th1 and Th17 in liver tissue). It was confirmed that the pathological condition of NASH in C57BL/6 mice that were fed an MCD was improved by suppressing the deterioration of IL-17-induced JNK-dependent lipotoxicity [389] . Astaxanthin is expected to suppress mitochondrial dysfunction in NAFLD [390] and protect against ischemia-reperfusion injury in fatty liver [391] .…”
Section: Changes In Immune Dynamics Owing To Therapeutic Intervention In Nafld Modelmentioning
confidence: 77%